Comparison of national innovation systems in the European Union countries - Edyta Dworak; Maria Magdalena Grzelak; Elżbieta Roszko-Wójtowicz (Risks, 2021)
The effective operation of national innovation systems can be a source of many opportunities, but it cannot be forgotten that innovation in itself may mean limiting but also generating various types of risks for the functioning of the local market. The main aim of the article is to present the concept and classification of national innovation systems in the world and to try to answer whether the type of NIS determines the level of innovation of the economies of the European Union countries. The following research thesis was formulated in the study: the type of National Innovation System determines a certain level of innovation in the economy of an European Union country, i.e., in countries belonging to a developed NIS, the level of innovation of the economy is higher than in countries belonging to developing systems. The results of the analysis confirm the research thesis. In the empirical part, the level of innovation in the European Union countries was assessed using the synthetic measure of development (SMD) by Z. Hellwig. Based on the obtained values of the synthetic measure of development (innovation), a ranking of the innovation of the economies of the EU countries was compiled and groups of countries with a similar degree of innovation in the economy were distinguished. The developed ranking of the European Union countries was compared with the NSI classification presented in the theoretical part of the article. The study covered 2010 and 2019.
Keywords: 330; innovation; national innovation system (NIS); Hellwig method; linear ordering; standard deviation method; European Union (EU); synthetic development measure (SDM)